The Influence of Knowledge, Minimum Capital, and Digital Technology on Investment Interest in the Sharia Capital Market Among Ponorogo Students - Rosa Nurhidayati; Ajeng Pipit Fitriani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to analyze the influence of knowledge, minimum investment capital, and digital technology on Ponorogo students' interest in investing in the Islamic capital market. This research methodology uses a quantitative approach, with data collection techniques using questionnaires. Statistical tests show that, both partially and simultaneously, knowledge, minimum investment capital, and digital technology have a positive and significant effect on students' investment interest. Adequate knowledge, the availability of affordable initial capital, and ease of access and transactions through digital technology have proven to be important factors driving students' interest in investing in the Islamic capital market.